Caffeic acid phenethyl ester, a promising component of propolis with a plethora of biological activities: A review on its anti‐inflammatory, neuroprotective, hepatoprotective, and cardioprotective effects. Issue 8 (11th July 2013) - Tolba, Mai F.; Azab, Samar S.; Khalifa, Amani E.; Abdel‐Rahman, Sherif Z.; Abdel‐Naim, Ashraf B.
Abstract Caffeic acid phenethyl ester (CAPE) is an important active component of honey bee propolis that possesses a plethora of biological activities. Propolis is used safely in traditional medicine as a dietary supplement for its therapeutic benefits. This review highlights the recently published data about CAPE bioavailability, anti‐inflammatory, neuroprotective; hepatoprotective and cardioprotective activities. CAPE showed promising efficacy both in vitro and in vivo studies in animal models with minimum adverse effects. Its effectiveness was demonstrated in multiple target organs. Despite this fact, it has not been yet investigated as a protective agent or a potential therapy in humans. Investigation of CAPE efficacy in clinical trials is strongly encouraged to elucidate its therapeutic benefit for different human diseases after performing full preclinical toxicological studies and gaining more insights into its pharmacokinetics. © 2013 IUBMB Life, 65(8):699–709, 2013